A influência da composição da remuneração aos acionistas sobre a capacidade informacional dos lucros contábeis nas ações listadas da Bm&fbovespa - Silva, Silvio Freitas da (2015)
This study aims to analyze the influence of the shareholders compensation composition on the informational capacity of accounting profits in the shares of companies listed on the BM & FBOVESPA. The sample was composed of 172 stocks of companies traded on the São Paulo Stock Exchange ranging the years of 2010 to 2014, with a total of 595 observations per variable. The data used in this research were obtained from information collected in a software database named Comdinheiro and the web site of BM & FBovespa. Regarding the main information, dividends and interest on equity, they were collected, promptly, in standardized financial statements available at the Brazilian SEC web site (CVM). It was found during the study that the total shareholders compensation, dividends and future compensation contribute positively to the informational capacity of accounting earnings for explaining the return of the shares of companies listed on the BM & FBovespa. In addition, it was found that at the time of release of the Cash Flow Statement, interest on equity and past salaries do not contribute to informational capacity of accounting profits, as they were already reflected in stock prices. Net income was positive and statistically significant in all models, as the main variable that impacts on stock returns, this result is consistent with the findings of Ball and Brown (1968), Beaver (1968) and Sarlo Neto (2009). It is suggested for further research on the relationship of the compositions of shareholders compensation and stock prices, the analysis considering factors such as specific regulatory sectors, ownership structure and type of controller.